Tafsir Surat Yusuf Ayat 23-24: (Studi Komparatif Tafsir Al-Misbah Dan Tafsir Hidayatul Qur’an) - Yusuf Fauzi; Achsanudtaqwin, Achris; Lutfi Abdul Manaf; Haris Syamsuddin (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2025)
The purpose of this study is to reveal how differences in interpretive methodology influence the understanding of temptation, moral resistance, and divine intervention during Prophet Yusuf’s encounter with the wife of the ruler of Egypt. Using a qualitative-comparative method and data analysis, the study finds that Quraish Shihab’s interpretation centers on ethical awareness and human willpower. Meanwhile, Afifuddin Dimyathi places greater emphasis on the spiritual dimension and divine protection as essential elements of moral salvation. The findings indicate that Qur’anic interpretation is influenced not only by methodology but also by the epistemological background of the exegete. This study contributes to the broader discourse of thematic exegesis and Qur’anic hermeneutics, particularly in exploring the roles of morality and spirituality when facing life’s trials, as illustrated in the story of Prophet Yusuf and the wife of Egypt’s ruler. Keywords : Surah Yusuf, Comparative Study, Tafsir Al-Misbah, Tafsir Hidayatul Qur’an